On the Latin American growth paradox: A hindsight into the Golden Age - Giorgia Barboni; Tania Treibich (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2010)
In 1950, Latin American countries capabilities were promising, and the subcontinent was thought to have a big potential for convergence. In order to understand why this prediction was not fulfilled, we apply in this paper the framework set by Fagerberg and Srholec (2008(24)). Our study of the economic evolution of Latin America during the Golden Age (1950-1975) is based on historical data on economic, political and social variables from 18 countries. We use a factor analysis to classify our 20 indicators into five dimensions: the level of industrialization, human capital, the macroeconomic fundamentals, politics and religion. We find that only the quality of human capital and the presence of Roman Catholics significantly and positively affected Latin American economic growth in this period, while the determinants traditionally put forward in the empirical growth literature, such as technical change and openness, did not. Finally, the positive correlation between the religion and education variables reveals that this result is partly related to the role of the Catholic Church as an educational institution.
Keywords: N26; O54; C38; 330; Growth; Development; Convergence; Factor Analysis; Latin America; Economic History; Golden Age; Wirtschaftswachstum; Faktorenanalyse; Lateinamerika